La dimension vocale de la propagande - Oksana Bulgakowa (Conserveries Mémorielles)
The vocal dimension of propagandaThe visual aspect of the propaganda films, the manipulation produced by montage, dramaturgy and the specific relation between the text of the comments and presented images attracted comprehensibly much more attention than the voice used in the war propaganda films. The recent historiography approaches the exam of the “vocal mechanisms” of indoctrination in the public sphere and the history of the national voice politics. This article contextualizes Soviet voices of some War Propaganda Films, the “disembodied voice of Soviet history”, situated at the intersection of the political, ideological, cultural and biological models. This article situates the voices of the speakers in the vocal landscape in the Soviet Union of this time as represented by the public voice of political figures and the professional voice of radio announcers and film actors. The binary opposition of public (pathetic, loud) vs. private (intimate, confiding, quiet) voices was very controversial during this period. The complexity of the Soviet vocal landscape of the propaganda can be understood and illuminated through a juxtaposition and comparison to the German strategies of vocal indoctrination or the American cultural politics of the voice.